1982
DOI: 10.1161/01.hyp.4.4.556
|View full text |Cite
|
Sign up to set email alerts
|

Streptozotocin diabetic rats are hypertensive despite reduced hypothalamic responsiveness.

Abstract: SUMMARY To determine whether diabetes predisposes rats to hypertension, tail-cuff systolic pressures were measured in male rats made diabetic by pretreatment with streptozotocin. From Weeks 2 through 7, diabetic rats weighed less but had higher systolic pressures than nondiabetic ones. Further comparisons made while the rats were anesthetized with urethane showed that pressor and sympathetic nerve responses to ventromedial hypothalamic stimulation, as well as pressor responses to injected vasopressin, were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
2
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 44 publications
(32 reference statements)
3
24
2
1
Order By: Relevance
“…However, this cannot be the full explanation of the present findings, since cardiac reflex responses to the pressor effects of vasopressin, angiotensin II or methoxamine are not reduced in STZtreated, Wistar rats (Hebden et al, 1987b). Several studies have reported on resting arterial blood pressure following STZ treatment; some have shown diabetic rats are hypertensive (Kawashima et al, 1978;Bunag et al, 1982;Funakawa et al, 1983), whereas others have found they are normotensive (Rodgers, 1986;Yamamoto, 1988) or hypotensive (Kohler et al, 1980;Hebden et al, 1987a;Kusaka et al, 1987;Tomlinson et al, 1989;1990). The difference between the results from this present study and our earlier studies, in which we reported hypotension in diabetic rats (Hebden et al, 1987a,b;Tomlinson et al, 1989;1990), is that previously both systolic and diastolic blood pressures were recorded, and it was systolic pressure which was consistently reduced (Hebden et al, 1987a;Tomlinson et al, 1989).…”
Section: Discussionmentioning
confidence: 53%
“…However, this cannot be the full explanation of the present findings, since cardiac reflex responses to the pressor effects of vasopressin, angiotensin II or methoxamine are not reduced in STZtreated, Wistar rats (Hebden et al, 1987b). Several studies have reported on resting arterial blood pressure following STZ treatment; some have shown diabetic rats are hypertensive (Kawashima et al, 1978;Bunag et al, 1982;Funakawa et al, 1983), whereas others have found they are normotensive (Rodgers, 1986;Yamamoto, 1988) or hypotensive (Kohler et al, 1980;Hebden et al, 1987a;Kusaka et al, 1987;Tomlinson et al, 1989;1990). The difference between the results from this present study and our earlier studies, in which we reported hypotension in diabetic rats (Hebden et al, 1987a,b;Tomlinson et al, 1989;1990), is that previously both systolic and diastolic blood pressures were recorded, and it was systolic pressure which was consistently reduced (Hebden et al, 1987a;Tomlinson et al, 1989).…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, electrical stimulation of the ventromedial hypothalamus elicited larger pressor and sympathetic nerve responses from insulin-treated rats than from untreated controls (table 4). Inasmuch as these changes are opposite to those produced during induction of diabetes, 10 our results imply that insulin treatment restores normal cardiovascular and hypothalamic function.…”
Section: Od-mentioning
confidence: 42%
“…Plasma vasopressin becomes elevated in diabetic patients as well as hypertensive rats, and upon finding pressor responses to vasopressin reduced in streptozotocin diabetic rats we suggested that reduced responsiveness may be due to receptor saturation. 10 An alternative mechanism based on impaired baroreceptor buffering has been proposed to explain enhancement of pressor responses to vasopressin after intracerebroventricular injection of angiotensin, 29 or in salt-sensitive genetically hypertensive rats. 30 Whatever the cause may be, our finding of larger pressor responses to vasopressin in insulin-treated than in untreated diabetic rats (table 5) supports the conclusion that cardiovascular dysfunction in diabetes can be effectively reversed by insulin.…”
Section: Od-mentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity is such that the small but significant difference in SBP between normal and diabetic rats 18 can be easily demonstrated. The designs for recording the differentiated impedance are relatively simple and can be constructed by most electrical engineering laboratories.…”
mentioning
confidence: 99%